Teaching Soft Skills to Business Students: An Analysis of Multiple Pedagogical Methods. (September 2016) - Anthony, Suzanne; Garner, Benjamin
Recent reports have suggested that many employees in the workforce today lack essential soft skills. This research analyzes the effectiveness of multiple classroom assignments for teaching soft skills in a Business Communication course. Five distinct pedagogical strategies were used in an effort to teach soft skills, including a self-analysis, an interview, a guest lecturer, a journal article, and a soft skills video. Results offer insights into students' perceptions of the most helpful pedagogical approaches for teaching soft skills.